Overview of Block Chain Cross Chain Technology - Lin, Shaofeng; Kong, Yihan; Nie, Shaotao (International Conference on Measuring Technology and Mechatronics Automation (Print), 2021)
With the continuous development of block chain technology, block chain is widely used in payment and settlement, product traceability, identity authentication and other fields. A large number of block chain networks with different characteristics and different scenarios have formed many value islands. The cross chain technology of block chain is an important technical means to realize the interconnection and value transfer between chains. This paper systematically summarizes the current mainstream cross chain technologies of block chain, analyzes the characteristics of different cross chain technologies, points out the challenges faced by cross chain technology, and forecasts its future development prospects.